Chemical Fingerprinting and Biological Evaluation of the Endemic Chilean Fruit Greigia Sphacelata (Ruiz and Pav.) Regel (Bromeliaceae) by Uhplc-Pda-Orbitrap-Mass Spectrometry - Echeverria-Morgado, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Greigia sphacelata (Ruiz and Pav.) Regel (Bromeliaceae) is a Chilean endemic plant popularly known as “quiscal” and produces an edible fruit consumed by the local Mapuche communities named as “chupón”. In this study, several metabolites including phenolic acids, organic acids, sugar derivatives, catechins, proanthocyanidins, fatty acids, iridoids, coumarins, benzophenone, flavonoids, and terpenes were identified in G. sphacelata fruits using ultrahigh performance liquid chromatography-photodiode array detection coupled with a Orbitrap mass spectrometry (UHPLC-PDA-Orbitrap-MS) analysis for the first time. The fruits showed moderate antioxidant capacities (i.e., 487.11 ± 26.22 µmol TE/g dry weight) in the stable radical DPPH assay, 169.08 ± 9.81 TE/g dry weight in the ferric reducing power assay, 190.32 ± 6.23 TE/g dry weight in the ABTS assay, and 76.46 ± 3.18% inhibition in the superoxide anion scavenging assay. The cholinesterase inhibitory potential was evaluated against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). From the findings, promising results were observed for pulp and seeds. Our findings suggest that G. sphacelata fruits are a rich source of diverse secondary metabolites with antioxidant capacities. In addition, the inhibitory effects against AChE and BChE suggest that natural products or food supplements derived from G. sphacelata fruits are of interest for their neuroprotective potential. © 2020 by the authors.